Analisis SWOT Berbasis Marketing Mix (7P) Sebagai Strategi Peningkatan Daya Saing Rumah Makan Campur-Campur di Jimbaran - I Wayan Restu Suarmana (CV. ITTC INDONESIA, 2026)
Increasing competition in the culinary business sector requires business owners to implement appropriate strategies to enhance their competitiveness. Rumah Makan Campur-Campur, as a culinary business located in Jimbaran, faces challenges such as intense competition, limited promotional activities, and the suboptimal utilization of digital technology in marketing efforts. This study aims to identify the internal and external factors affecting the business and to formulate appropriate strategies for improving competitiveness through a SWOT analysis based on the Marketing Mix (7P) approach. This research employed a descriptive qualitative method, with data collected through interviews, observations, and documentation. The analysis was conducted by identifying internal factors based on the Marketing Mix (7P) elements, namely Product, Price, Place, Promotion, People, Process, and Physical Evidence, as well as external factors in the form of opportunities and threats. These factors were analyzed using the IFAS and EFAS matrices and subsequently formulated into a SWOT matrix. The results indicate that Rumah Makan Campur-Campur possesses several strengths, including a diverse menu selection, distinctive flavors, a strategic location, prompt service, and a unique traditional atmosphere. The identified weaknesses include limited digital promotion and inadequate supporting facilities. The IFAS and EFAS analyses produced coordinates of (+1.75; +0.69), placing the business in Quadrant I (Growth Strategy). Therefore, the recommended strategy is an aggressive (SO) strategy that focuses on strengthening the restaurant’s positioning as a traditional culinary destination, enhancing digital marketing activities, and developing product and service innovations to improve competitiveness sustainably.